2018
DOI: 10.1111/jsr.12714
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behaviour and sleep problems among 42,489 community‐dwelling adults in six low‐ and middle‐income countries

Abstract: There is a lack of multinational research investigating the association between sleep problems and sedentary behaviour. In this study, we investigated the relationship between the time spent sedentary during waking hours and sleep problems in six low- and middle-income countries. Cross-sectional, community-based data from the Study on Global Ageing and Adult Health survey were analysed. Adjusted logistic regression analyses were undertaken to explore the relationship between self-reported sleep problems (such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 33 publications
1
29
0
2
Order By: Relevance
“…In line with our findings, a recent meta-analysis indicated no independent associations between SB and SQ but did demonstrate associations with other sleep outcomes [10]. More recent results from two large observational studies in generally healthy adults indicated that when the self-reported SB was high, the odds of reporting poor SQ/sleep problems nearly doubled [11,12]. Loprinzi et al examined data (N = 5563) from a large US sample of adults using objectively measured SB [7].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with our findings, a recent meta-analysis indicated no independent associations between SB and SQ but did demonstrate associations with other sleep outcomes [10]. More recent results from two large observational studies in generally healthy adults indicated that when the self-reported SB was high, the odds of reporting poor SQ/sleep problems nearly doubled [11,12]. Loprinzi et al examined data (N = 5563) from a large US sample of adults using objectively measured SB [7].…”
Section: Discussionsupporting
confidence: 88%
“…A meta-analysis found SB to be associated with an increased risk of insomnia and sleep disturbance but not daytime sleepiness and poor SQ in adults [10]. More recent results from observational studies suggest an independent relationship with SB and SQ [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis found that sedentary time is associated with an increased risk of insomnia (pooled OR 1.18, 95% CI: 1.01-1.36) and sleep disturbance (1.38, 95%CI: 1.28-1.49) [21]. Additionally, Vancampfort et al found that sedentary time was associated with sleep disturbances among 42,489 adults [24]. This relationship was the strongest in adults 50-64 years old, highlighting the potential importance of sedentary time in an aging population like postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is a paucity of literature on whether exercise intensity is associated with indices of sleep. Higher levels of sedentary time, which are common among postmenopausal women [19,20], are also associated with poor sleep efficiency, insomnia, and sleep disturbances [21][22][23][24][25]. Thus, there is a strong need to understand the associations between physical activity, sedentary time, and sleep, which may help inform lifestyle strategies for reducing the risk of chronic disease following menopause.…”
Section: Introductionmentioning
confidence: 99%
“…This may include time spent sitting at a desk, visiting friends, reading, or sitting or lying down to watch television." Sedentary time was categorized into < 4 hours, 4 ≤ 8 hours, 8 ≤ 11 hours, and 11 or more hours a day (15).…”
Section: Exposure Variablesmentioning
confidence: 99%